Verification of radioecological models to the instrumental data of the specific activity 131I in a grass in Mazovia and Bohemia after the Chernobyl accident (from “Prague” and “Warsaw” scenarios of the IAEA project EMRAS - Oleg K. Vlasov; Pavel Krajewski; Irina A. Zvonova; Irena Malatova; Miluse Bartuskova; Nataliya V. Schukina; Sergey Yu. Chekin; Konstantin A. Tumanov (Радиационная гигиена)
The analysis of instrumental data of “Prague” and “Warsaw” scenarios on the dynamics of 131I specific activities in the grass is carried out. Reconstruction of the 131I the specific activities dynamics in the grass in the Mazovia and Bohemia localities is performed in three models: direct calculation the input data of the “Prague” and “Warsaw” scenarios, homogeneous cloud, heterogeneous rain and heterogeneous cloudhomogeneousrain. The actual 137Cs fallout densities in the grass sampling sites in average more than 2.9 times for Prague and 2 times for Warsaw. Effective rain during the main fallout at the grass sampling sites, reconstructed on the model of a homogeneous cloud is 3–4 times more than at the nearest weather stations during this time. A realistic scenario of the input data leading to the optimal agreement of the calculated and instrumental data is revealed. It is shown that direct calculations and the homogeneous cloud model give almost identical results and lead to a significantly better agreement with the instrumental data than the an inhomogeneous cloud model. The calculated and instrumental data show a significant decrease in the 131I specific activity in the grass after the end of the main fallout due to its flushing from the grass surface by strong prolonged rain 13 and 19 days after the accident in Mazovia and 30 and 35 days in Bohemia. Uncertainties in the results of reconstruction of the dynamics of 131I and 137Cs activities in vegetation are estimated. The meangeometric values and standard mean-geometric deviations of the calculation/ 8instrumental data ratios are: 0.8–1.1 and 1.8–1.9 for grass.